ANALYSIS OF RISK FACTORS FOR PREGNANT WOMEN INFECTED WITH MALARIA: Analisis Faktor Resiko Ibu Hamil Yang Terinfeksi Malaria - Rahmadhani, Wulan; Aprina, Hardianti; Chamroen, Pall; Soe, Than Kyaw (Universitas Airlangga, 2025)
Background: Malaria is a disease caused by protozoa infection of the genus Plasmodium transmitted through the bite of infected female Anopheles mosquitos. Malaria infection in pregnancy is detrimental to both the mother and the fetus. Several efforts to prevent and eradicate malaria have been implemented, but many pregnant women are still infected with malaria. Purpose: To know the risk factors for pregnant women infected with malaria. Methods: This study used the literature review method by searching for articles analyzing risk factors for pregnant women infected with malaria. Articles were searched from two databases, namely PubMed and Google Scholar. The keywords used are